The Influence Of Customer Experience And Product Quality On Customer Satisfaction Through Buying Decisions For Eiger Outdoor Gear Products In Pekanbaru City - Asrilsyak, Sharnuke (Pusat P2M Politeknik Negeri Batam, 2024)
This study was conducted with the aim of knowing the effect of Customer Experience and Product Quality on Customer Satisfaction through Buying Decisions in the Pekanbaru city community. The population in this study were the people of Pekanbaru city who had shopped at Eierg products in Pekanbaru City. Sampling in this study was carried out using the purposive sampling technique, so the number of samples in this study was 135 respondents. The data analysis method of this study uses the Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis method with SmartPLS software version 4.1.0.2. The results showed a positive and significant influence between customer experience and Buying Decisions. There is a positive and significant influence between Product Quality and Buying Decisions. There is a positive and significant influence between Buying Decisions and Customer Satisfaction. There is a positive and significant influence between customer experience and Customer Satisfaction through Buying Decisions. There is a positive and significant influence of social media marketing on consumer satisfaction through Buying Decisions.